Arquitetura deposicional e compartimentação estrutural do Aquífero Passo das Tropas na região de Santa Maria-RS: influências no comportamento hidrogeológico - Wankler, Fábio Luiz (Universidade do Vale do Rio dos Sinos, 2006)
This thesis presents a multi-scale analysis of the Passo das Tropas Aquifer in the Santa Maria region aiming to identify giga- to macro scale, vertical and horizontal hetereogeneities. The Passo das Tropas Member (Middle Triassic of the Parana Basin) comprises a 20 to 30 m thick sandstone package deposited over an area of 2.428,92 Km² within an extensional basin (half graben). Employed method include geological mapping (giga- and mega-scale), outcrop and well log (gamma-ray) correlation, 3D modeling (mega- and meso-scale), facies analysis (meso-scale) and Ground Penetrating Radar (meso-scale) interpretation. The Passo das Tropas fluvial system represent the onset of the neo- to meso- Triassic sedimentation during wich multi-episodic, channel belt fills were superimposed. At this time, the fluvial systemwas perennial and braided, and former under steady subsidence rates on an extensional basin (half graben). This system was subdivided into two low accommodation rate system tracts (São Valentim and Sarandi subunits) that include deposits of axial and transversal fluvial systems, respectively. The boundary between both units is a regional-scale, secondary expansion surfasse that occur as a discontinuous bed of argillite of intraformacional conglomerate. Each subunit presents an internal architecture characterized by the superposition of tabular bodies or lenses bounded by 5th order surfaces. Acquired information indicates that the Passo das Tropas Aquifer encompasses two main aquifer types: a first one characterized by a set of small unconfined aquifers located on topographic highs on the southern and southwestern portions of the study area and a second one formed by a confined aquifer located on the northwestern region of the same study area. Both types of aquifers were further affected by NW-SE and NE-SW fault systems (up to 20 m of vertical displacement) that segmented them into structural blocks and sub-blocks, with deformation zones displaying deformation belts, drag folds, fault breccias and shale smears. The hierarquical classification of the vertical and horizontal heterogeneities and anisotropies of Passo das Tropas Aquifers led to the elaboration of a hydrogeological conceptual (qualitative) model.
Keywords: Geologia; Aquífero Passo das Tropas; Comportamento hidrogeológico; Arquitetura deposicional; ACCNPQ::Ciências Exatas e da Terra::Geologia